Assembly of four new cobalt coordination polymers modulated by N-coligands: sensitive and selective sensing of nitroaromatics, Fe3+ and Cr2O72− in water. Issue 10 (14th February 2020) - Tu, Qian-Qian; Ren, Ling-Ling; Cui, Ying-Ying; Cheng, Ai-Ling; Gao, En-Qing
Abstract : Four new Co-CPs (1 to 4 ) have been obtained with the modulation of N-coligands. 2 and 3 can serve as multi-responsive sensors for rapid and sensitive detection of nitroaromatics, Fe 3+ and Cr2 O7 2− in water. Abstract : Four new Co coordination polymers (CPs), formulated as [Co(L)(phen)] (1, 1D), [Co3 (L)3 (phen)2 ·4H2 O] (2, 2D), [Co3 (L)3 (2, 2′-bipy)2 ·8H2 O] (3, 2D) and [Co2 (L)3 (4, 4′-bipy)2 ·] (4, 3D) (H2 L = 6-methoxy-2, 2′-sulfone-4, 4′-dicarboxylic acid, phen = 1, 10-phenanthroline, 2, 2′-bipy = 2, 2′-bipyridine, 4, 4′-bipy = 4, 4′-bipyridine), have been solvothermally synthesized based on a functional dicarboxylate bridging ligand in the presence of various N-coligands. Complex 1 features a 3D supramolecular architecture composed of parallel linear chains assembled via π–π interactions. Complexes 2 and 3 have similar structures, which are both (4, 4)-connected 2D networks possessing 1D channels based on linear trinuclear [Zn3 (CO2 )6 N4 ] clusters. Complex 4 contains (4, 4)-connected 2D layers based on binuclear clusters, which are further linked into a 3D pillar-layered framework by 4, 4′-bipy. Luminescence studies indicate that 2 and 3 both show strong fluorescence and good stability in water, and they can be used as multi-responsive sensors for selective sensing of nitroaromatics, Fe 3+ and Cr2 O7 2− in water via luminescence quenching with fast response. Remarkably, 2 and 3 can be conveniently regenerated for at least four times without sacrificing their quenching efficiencies. The possible mechanisms for the luminescence quenching have been investigated in detail.